ANALISIS SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA RUMAH SAKIT DI UPTD RSUD PANDAN KABUPATEN TAPANULI TENGAH TAHUN 2022 - Paskah Sulastri Sihotang (Jurnal Kajian Kesehatan Masyarakat, 2023)
According to the Ministry of National Labor of the Republic of Indonesia regarding the Implementation of the Occupational Safety and Health Management System which aims to create safe, safe and comfortable working environment conditions, and be free from the risk of danger that may arise and in turn the company will obtain healthy and productive workers. Thus, the UPTD of Pandan Regional Hospital, Central Tapanuli Regency, is one of the hospitals that have a risk of danger, so it must be anticipated by implementing an Occupational Safety and Health Management System. Therefore, the implementation and management are expected to anticipate risks that do not need to occur, which will increase efficiency and improve K3 performance. The method used in this research is the Mixed Method, which is a combination of quantitative and qualitative methods in one study. The results of this study are presented by conveying the categories of research results which will then be clarified by describing the results of information or the results of in-depth interviews. Based on the results of interview data and checklists conducted in accordance with PP 50 of 2012 concerning SMK3, the following is a recapitulation of the level of compliance of each element based on the results of the K3 Management System audit for the success rate of achieving the occupational safety and health management system of hospitals at UPTD Pandan Hospital, Central Tapanuli Regency is 46.87%, which is secured the Success Rate Category is still Less (0- 59.9%).